The outcomes of polyparasitism in stray cats from Brazilian Midwest assessed by epidemiological, hematological and pathological data - Silva, Alanderson Rodrigues da; Andrade, Gisele Braziliano; Carvalho, Joyce Katiuccia Medeiros Ramos; Barreto, Wanessa Teixeira Gomes; Santos, Filipe Martins; Sousa, Keyla Carstens Marques de [UNESP]; André, Marcos Rogério [UNESP]; Ferreira, Luiz Claudio; Menezes, Rodrigo Caldas; Herrera, Heitor Miraglia (FapUNIFESP (SciELO), 2022)
We evaluated the epidemiological, hematological, and pathological data of Leishmania spp., Toxoplasma gondii, Platynosomum illiciens, feline immunodeficiency virus (FIV), and feline leukemia virus (FeLV) infections and the coinfections in stray cats of an endemic area for leishmaniasis. The diagnosis was performed by serological tests and necropsy. We described gross lesions and histopathological findings. We used immunohistochemistry and chromogenic in situ hybridization for L. infantum detection. We found infection in 27 out of 50 sampled cats, among them, 14 presented coinfections. A strong correlation between splenomegaly and lymphadenomegaly with FeLV, and an association between hepatic lesions and cachexia with parasitism due to P. illiciens were observed. Moreover, we found a significant increase in the monocyte count in the FeLV-infected and a decrease in the red blood cell count in the FIV-infected animals. Amastigote forms of Leishmania spp. and tissue changes were detected in lymphoid organs of an animal coinfected with P. illiciens, T. gondii, and FIV. Polyparasitism recorded in stray cats of the Brazilian Midwest should be considered in effective control strategies for public health diseases. Moreover, stray cats of Campo Grande may be a source of infection of FIV, FeLV and P. illiciens for populations of domiciled cats.
Poliparasitismo em gatos não domiciliados no Centro-Oeste brasileiro avaliado através dos aspectos epidemiológicos, hematológicos e patológicos
Keywords: Feline Immunodeficiency virus; Feline Leukemia virus; in situ hybridization; Platynosomum illiciens; Toxoplasma gondii